ANALYSIS OF THE STATIC AND DYNAMIC CHARACTERISTICS OF THE TOOL POST NARA 4308 LATHE MACHINE - Saka Bhaskara, Rasyid
Machining processes are among the most used methods in manufacturing. Various types of machining are performed using different tools, one of which is the lathe machine. Lathes are used in manufacturing to reduce the dimensions of cylindrical objects, create threads, and perform other operations. Considering the significant export value of lathe machines from Indonesia, this study aims to evaluate the static and dynamic characteristics of the NARA 4308 lathe machine, which was donated by the South Korean government. This final project research explains the static and dynamic characteristics of the tool post on the NARA 4308 lathe. The study determines the static stiffness and dynamic characteristics through simulations using SOLIDWORKS for 3D design and ANSYS for simulation analysis. The results of this Final Project research show that the static stiffness value of the tool post of the NARA 4308 lathe machine is 2.48 MN/mm. For static stiffness, the values are 1.92 MN/mm on the X-axis, 21.41 MN/mm on the Y-axis, and 34.96 MN/mm on the Zaxis. The dynamic simulation testing will indicate the receptance values. On the X-axis, the receptance is 0.62594 ?m/N at a natural frequency of 2195 Hz, on the Y-axis it is 0.26063 ?m/N at a natural frequency of 2090 Hz, and on the Z-axis, it is 15.212 ?m/N at a natural frequency of 1640 Hz.